Supercompensated glycogen loads persist 5 days in resting trained cyclists - Arnall, D. A.; Nelson, A. G.; Quigley, J.; Lex, S.; DeHart (European Journal of Applied Physiology, 2007)
Research data indicates a persistence of elevated muscle glycogen concentration 3 days post-supercompensation in resting athletes. This study expands our earlier findings by determining whether muscle glycogen remains elevated 3, 5, or 7 days post-supercompensation. Seventeen trained male cyclists underwent one bout of exhaustive exercise to deplete muscle glycogen. This was followed by a 3-day consumption of a high carbohydrate/low protein/low fat diet (85:08:07%). Three post-loading phases followed with subjects randomly assigned to either a 3-day, 5-day, or 7-day post-loading maintenance diet of 60% carbohydrate and limited physical activity. Biopsies (50-150 mg) of the vastus lateralis were obtained pre-load (BASELINE), at peak-load (PEAK), and either at 3-day, 5-day, or 7-day post-load (POST). On average, PEAK to POST muscle glycogen concentrations decreased 34, 20 and 46% respectively for the 3-, 5-, and 7-day POST groups. Only the 7-day post-load group`s PEAK to POST mean muscle glycogen concentration decreased significantly. In addition, multi-regression analysis indicated that the PEAK glycogen level was the main determinant of the number of days that glycogen levels remained significantly greater than BASELINE. Thus, trained athletes` supercompensated glycogen levels can remain higher than normal for up to 5 days post-loading. The amount of carbohydrate consumed, the level of physical activity, and the magnitude of the glycogen supercompensation determine the interval for which the glycogen levels are elevated.